Analysis of Supply Chain in Corn Commodities at Dompu District West Nusa Tenggara Province - Kurniawan, Dodo; Fajri, Candra Ananda; Adi S, Putu Mahardika; Khusaini, Khusaini (International Journal of Supply Chain Management, 2020)
The drastic drop in prices often does not merely reflect a surge in supply which is not accompanied by an increase in demand in an equal proportion, but also reflects a supply chain that is not well developed. The purpose of this study was to analyze the supply chain and supply chain margins for maize commodity in Dompu Regency, West Nusa Tenggara. The research method used a descriptive quantitative approach involving 120 corn farmers as respondents. This study uses supply chain margin analysis and Farmer's Share. The results showed that there were three types of supply chains, namely (1) Farmer-VCT-DCT-Wholesaler-PMT, (2) Farmer-DCT-Wholesaler-PMT, (3) Farmer-Wholesaler-PMT. Of the three supply chains 46% of farmers use the second supply chain, namely Farmers-DCT-Wholesaler-PMT. The supply chain that has a small margin and a high farmer's share is the third supply chain, with a supply chain margin of IDR 613 and a farmer's share of 85.22%.Keywords: Supply chain, Corn, Dompu.